2004
DOI: 10.1111/j.1464-410x.2004.05161.x
|View full text |Cite
|
Sign up to set email alerts
|

Erectile response with vardenafil in sildenafil nonresponders: a multicentre, double‐blind, 12‐week, flexible‐dose, placebo‐controlled erectile dysfunction clinical trial

Abstract: Associate Editor Michael G. Wyllie Editorial Board Ian Eardley, UK Jean Fourcroy, USA Sidney Glina, Brazil Julia Heiman, USA Chris McMahon, Australia Bob Millar, UK Alvaro Morales, Canada Michael Perelman, USA OBJECTIVE To evaluate the efficacy of vardenafil in patients previously unresponsive to sildenafil. PATIENTS AND METHODS A multicentre, double‐blind, 12‐week, flexible‐dose, placebo‐controlled trial was conducted, involving 463 men aged ≥ 18 years with moderate‐to‐severe erectile dysfunction (ED) and who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 31 publications
(43 reference statements)
0
40
0
2
Order By: Relevance
“…Therefore, compared with the placebo groups, the IIEF score for patients who received PDE-5 inhibitors increased by ≥ 9 points. At present, an increase of 5 points is 16 Therefore, the data suggest that PDE-5 inhibitors are an effective treatment for ED after kidney transplant. The Global Efficacy Questionnaire showed that 66% of renal transplant recipients believed that treatment had improved their erections (patients who were not transplant recipients, 73%).…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, compared with the placebo groups, the IIEF score for patients who received PDE-5 inhibitors increased by ≥ 9 points. At present, an increase of 5 points is 16 Therefore, the data suggest that PDE-5 inhibitors are an effective treatment for ED after kidney transplant. The Global Efficacy Questionnaire showed that 66% of renal transplant recipients believed that treatment had improved their erections (patients who were not transplant recipients, 73%).…”
Section: Discussionmentioning
confidence: 88%
“…The study enrolled 463 men with ED unresponsive to sildenafil (no response in at least four of six attempts with sildenafil) to vardenafil 10 mg (that could be titrated to 5 or 20 mg) or placebo. 127 Compared to placebo, the percentage of penetrations (30 vs 62%) and successful intercourse (11 vs 46%) was higher with vardenafil. 127 Also, this study shown that vardenafil was more effective than placebo from after 0.25 h until beyond 6 h. 128 In order to replace sildenafil in the treatment of ED, vardenafil will have to be shown to be superior to sildenafil.…”
Section: Clinical Trials With Vardenafilmentioning
confidence: 99%
“…127 Compared to placebo, the percentage of penetrations (30 vs 62%) and successful intercourse (11 vs 46%) was higher with vardenafil. 127 Also, this study shown that vardenafil was more effective than placebo from after 0.25 h until beyond 6 h. 128 In order to replace sildenafil in the treatment of ED, vardenafil will have to be shown to be superior to sildenafil. To date, there are no obvious major differences between sildenafil and vardenafil.…”
Section: Clinical Trials With Vardenafilmentioning
confidence: 99%
“…Changing the type of PDE5 inhibitors for nonresponders has typically had less drastic results. 30 Another difficult-to-treat group are patients with comorbidities such as coronary artery disease and diabetes. Mirone et al 31 compared two different dosing regimens in 4262 subjects.…”
Section: Biological Evidence Supporting the Use Continuous Pde5 Inhibmentioning
confidence: 99%